1999
DOI: 10.1002/(sici)1097-461x(1999)71:2<133::aid-qua2>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

The electron-pair origin of antiaromaticity: Spectroscopic manifestations

Abstract: ABSTRACT:It is shown that the antiaromatic character of certain conjugated cyclic hydrocarbons is due to the presence of an even number of distinct electron pairs in the Ž . system such as, but not necessarily electrons . In these systems, the ground state is Ž . constructed from an out-of-phase combination of two valence bond VB structures, and its equilibrium geometry is necessarily distorted along the coordinate that interchanges these structures. If a new symmetry element appears during the transition betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
63
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(70 citation statements)
references
References 30 publications
(1 reference statement)
6
63
1
Order By: Relevance
“…This suggests that the system is an important factor in the determination of the geometry, which can be understood in terms of the model given by Shaik et al [17][18][19][20][21][22][23]. Zilberg and Haas [25] stated that the geometric distortion of cyclobutadiene is a fundamental property of 4n electron ring systems. This is not the case according to our calculations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the system is an important factor in the determination of the geometry, which can be understood in terms of the model given by Shaik et al [17][18][19][20][21][22][23]. Zilberg and Haas [25] stated that the geometric distortion of cyclobutadiene is a fundamental property of 4n electron ring systems. This is not the case according to our calculations.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Zilberg and Haas [25] investigated the VB model from a fundamental perspective by examining the interaction between the Kekulé structures of systems with 4n and 4nϩ2 electrons. Using this approach, they found that the sign and the absolute size of the interaction alternate between the systems.…”
Section: Introductionmentioning
confidence: 99%
“…For the two VB functions used in Ref. 1, we find that the ground state is always a superposition with positive sign (at least in the simple semi‐empirical model employed), independent of whether the compound is aromatic or anti‐aromatic.…”
Section: Introductionmentioning
confidence: 75%
“…This Comment refers to the article “The Electron‐Pair Origin of Anti‐aromaticity: Spectroscopic Manifestations” by Shmuel Zilberg and Yehuda Haas 1. In that article, the electronic ground state of aromatic and anti‐aromatic compounds is expressed in terms of only two valence bond (VB) functions that correspond to the classical Kekulé structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation